Request diversion: a novel mechanism to counter P2P based DDoS attacks. (12th April 2010) - Al-Duwairi, Basheer; Mustafa, Abdul-Raheem Masoud
P2P-based distributed denial of service (DDoS) attacks represent an emerging threat for today's internet. This type of attacks exploits a design vulnerability of P2P networks in such a way as to drive as many P2P users as possible to download certain popular file(s) from a targeted host. This paper proposes a novel scheme, called request diversion, to counter DDoS attacks originating from P2P networks. The main idea of the proposed scheme is to divert P2P users from requesting a file that is advertised originally by an attacker to be available at the targeted host. This is achieved by intentionally making fake advertisements about the availability of the same file at different locations. The performance of the proposed scheme was evaluated through extensive simulation experiments. Simulation results show that request diversion scheme can reduce attack request rate drastically without being exploited by malicious users and without modifying the P2P clients and protocols.